Students' Perspectives on the Ideal Teacher in Lalitpur, Nepal (Pragyaratna प्रज्ञारत्न, 2024)
This study explored students' perspectives on the characteristics of an ideal teacher in Lalitpur, Nepal. The objective was twofold: to examine students' views on the ideal teacher and to determine whether these perspectives varied based on academic performance. A phenomenological research design was employed, focusing on two secondary-level students from Lalitpur. One student was a high academic achiever, while the other struggled academically. In-depth interviews were conducted, and the data were analyzed using thematic analysis. The results revealed that students viewed ideal teachers as those who actively engaged with less interactive and academically struggling students, offering support and encouragement. In contrast, ineffective teachers were described as those who overwhelmed students with unnecessary workloads, lacked creativity, and frequently reprimanded them for their performance. The practical implications of this study's findings underscore the importance of fostering inclusive and supportive learning environments tailored to the needs of all students, regardless of their academic abilities, providing actionable insights for educators, researchers, and policymakers.